2010
DOI: 10.4103/0975-3583.64441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular disease risk factors in people of Asian Indian origin: Age and sex variation

Abstract: Background:No study has been undertaken on people of Asian Indian origin to investigate the age and sex variation in the prevalence of cardiovascular disease (CVD) risk factors.Objectives:To investigate the age and sex variation in the prevalence of CVD risk factors among the people of Asian Indian origin.Materials and Methods:A total of 682 (302 males and 380 females) participants aged 25–85 years took part in the study. The subjects were categorized into 4 groups, namely, Group I (25–34 years), Group II (35–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We recognized age as an important contributor of the increase of CVD risk factors across the ages, independent of lifestyle, and dietary habits. Previous studies have also shown a positive relationship between age and CVD risk factors (e.g., waist circumference, WHtR, blood pressure, triglycerides, and LDL-C)[ 6 ] and also between age and CVD events. [ 16 ] In fact, age has been suggested as an inexpensive screening tool for detection of people at risk of future CVD events.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We recognized age as an important contributor of the increase of CVD risk factors across the ages, independent of lifestyle, and dietary habits. Previous studies have also shown a positive relationship between age and CVD risk factors (e.g., waist circumference, WHtR, blood pressure, triglycerides, and LDL-C)[ 6 ] and also between age and CVD events. [ 16 ] In fact, age has been suggested as an inexpensive screening tool for detection of people at risk of future CVD events.…”
Section: Discussionmentioning
confidence: 98%
“…[ 5 ] However, evidence indicates that cardiovascular risk factors start to increase even earlier, for example, in 20s. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Similar to findings reported in a previous national study in Malaysia [ 41 ], Indians were associated with the highest risk of overweight/obesity among the different ethnic groups. Genetic predispositions to overweight or obesity among Indians and other environmental factors, including behavioral and cultural influences on food preparation and consumption, could increase their susceptibility to obesity [ 42 ]. Among men, the upper middle-age group (40 to 49 years old) was more likely to be overweight/obese, and the likelihood decreased in the elderly (≥ 60 years old) compared to their younger (18 to 29 years old) counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of an adverse impact of TFA:SFA intake and inverse relation of adiposity with PUFA, i.e., protection of polyunsaturated fat concerning the association with MS is in accordance with the finding of several other investigations. [ 23 26 29 ]…”
Section: Discussionmentioning
confidence: 99%